The Relationship between Anxiety and Self-Efficacy Among Post Cesarean Patients at Bhayangkara Hospital Jambi - Febrina; Mekeama, Luri; Yuliana, Yuliana (Program Studi Keperawatan Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2025)
Anxiety is a common emotional response experienced by post-operative patients, such as those undergoing cesarean section. Primigravida mothers are more vulnerable to anxiety due to pain, the recovery process, and fear of medical procedures. One psychological factor that plays a role in reducing anxiety is self-efficacy, which refers to an individual's belief in their ability to cope with difficult situations. Low self-efficacy can increase anxiety and hinder the recovery process. This study aimed to determine the relationship between anxiety and self-efficacy in post-operative cesarean section mothers. This research is a quantitative study with a cross-sectional approach. A sample of 105 post-operative cesarean section mothers on the first day post-surgery was selected using purposive sampling technique. The variables studied included anxiety (independent) and self-efficacy (dependent). The Hamilton Anxiety Rating Scale (HARS) was used to assess anxiety, while the General Self-Efficacy Scale (GSE) was employed to measure self-efficacy. Data were analyzed using the Spearman Rho correlation test. Statistical analysis using the Spearman Rho test indicated a significant relationship between anxiety levels and self-efficacy in post-operative cesarean section mothers, with a p-value of 0.000 and r = -0.771. The study revealed that the majority of respondents experienced moderate anxiety and low self-efficacy. A significant negative relationship was found between anxiety and self-efficacy (p < 0.05), indicating that higher anxiety levels were associated with lower self-efficacy. It can be concluded that self-efficacy plays an important role in reducing anxiety in postoperative cesarean section patients.